Evaluating Patient Experience with Integrated Virtual Care (IVC), a Hybrid Primary Care Model in Rural Ontario, Canada: A Cross-Sectional Survey - Samantha Buchanan; Shawna Cronin; Antoine St-Amant; Jonathan Fitzsimon (Journal of Primary Care & Community Health)
Introduction: Canada faces a primary care crisis, especially in rural regions. In Ontario, the innovative, Integrated Virtual Care (IVC) program is a hybrid care model that enrolls patients with a family physician working predominantly remotely, while also embedded in a local Family Health Team, blending virtual and in-person care. Objective: To evaluate the experience of patients enrolled in IVC. Methods: We conducted a cross-sectional survey in a rural region in eastern Ontario, Canada. Participants included individuals enrolled in IVC for a minimum of 6 months. Primary outcome measures focused on patient experience with IVC, including satisfaction, access, self-reported health, and healthcare utilization. We also examined representativeness of survey respondents. Results: 198 of 790 patients responded (response rate of 25.1%). Overall satisfaction was high, with 85% reporting being very satisfied or satisfied with IVC. Experiencing issues with virtual care was significantly associated with satisfaction. Survey respondents were generally older, Caucasian, and higher users of the healthcare system compared to a group of all those eligible to complete the survey. Conclusion: This study indicates high patient satisfaction with IVC among survey respondents. These insights can inform the expansion of innovative hybrid care models to meet the needs of underserved, rural populations.